2020
DOI: 10.1177/1076029620960820
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies on the Anticoagulant Profile of Branded Enoxaparin and a New Biosimilar Version

Abstract: Low molecular weight heparins (LMWH) represent depolymerized heparin prepared by various methods that exhibit differential, biochemical and pharmacological profiles. Enoxaparin is prepared by benzylation followed by alkaline depolymerization of porcine heparin. Upon the expiration of its patent, several biosimilar versions of enoxaparin have become available. Heparinox (Sodic enoxaparine; Cristália Produtos Químicos Farmacêuticos LTDA, Sao Paulo, Brazil) is a new biosimilar form of enoxaparin. We assessed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Enoxaparin Cristalia was as effective as branded enoxaparin to prevent VTED [ 38 ]. In 2020, Qneibi et al [ 21 ] concluded that Heparinox (a new biosimilar) was bioequivalent to the original branded enoxaparin based upon in vitro tests. In 2021, Fantoni et al [ 39 ] conducted an observational, retrospective study to assess the safety and effectiveness of Inhixa in preventing VTED in medical and surgical inpatients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enoxaparin Cristalia was as effective as branded enoxaparin to prevent VTED [ 38 ]. In 2020, Qneibi et al [ 21 ] concluded that Heparinox (a new biosimilar) was bioequivalent to the original branded enoxaparin based upon in vitro tests. In 2021, Fantoni et al [ 39 ] conducted an observational, retrospective study to assess the safety and effectiveness of Inhixa in preventing VTED in medical and surgical inpatients.…”
Section: Discussionmentioning
confidence: 99%
“…Several biosimilar versions of Lovenox ® (Sanofi, Paris, France), the original branded form of enoxaparin, have become available for clinical use for the indications that Lovenox ® was previously approved [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two types of heparins are used in clinical practice: unfractionated heparins (UFH) and low molecular weight heparins (LMWH) [ 19 , 20 ].…”
Section: Anticoagulantsmentioning
confidence: 99%
“…When administered intravenously, the anticoagulant effect occurs immediately after injection. The drugs residence time depends on the administered dose and may range from 1–5 h. When injected subcutaneously, the anticoagulant effect occurs after 2–4 h [ 1 , 15 , 19 , 20 ].…”
Section: Anticoagulantsmentioning
confidence: 99%
See 1 more Smart Citation